Adequacy of Inflation-Indexed Life Annuity: A Case of Defined Contribution Pension Plan in Malaysia (Journal of Computational Innovation and Analytics (JCIA), 2025)
Defined Contribution (DC) pension plans in some Asian countries are currently operated by the lump-sum withdrawal scheme, which allows retirees to withdraw all accrued savings in a single withdrawal. This type of withdrawal does not protect pensioners from the longevity risk. This study examines the adequacy of an alternative for the lump-sum withdrawal system, namely the withdrawal system based on the Inflation-Indexed Life Annuity (IILA). This study proposes two types of IILA: the immediate IILA and the deferred IILA. The adequacy of a life annuity is measured using the ratio of projected wealth to the projected consumption at the retirement age. For the deferred IILA, this study uses the Euler-Lagrange method to assess the optimal amount that will be set aside to finance the annuity scheme. The IILA and deferred IILA will protect retirees from purchasing under-valued annuities by adjusting the IILA to inflation risk. Furthermore, deferred IILA may improve the life quality of retirees by providing adequate retirement income during the deferment years. Analysis of data from the Household Income and Expenditure Survey (HEIS, 2014) indicates that the immediate IILA offers an average lifetime income of over 50%, while the deferred IILA provides more than 40%.